Attempt to approach the constituent myths of the novels of Tahar Djaout - BENZELIKHA , Ahmed (Journal of Human Sciences, 2023)
Through the examination of the novel of Tahar Djaout, it’s a question of managing to identify the constituent myths. This involves three approaches, the first, general, consisting of an apprehension of literature as a place where myth arises.The second describes myths, such as that of the quest, creation and wandering, then the relationship of myth with childhood and finally the formation of the protesting “I”.The third, analytical, through the examination of the functioning of the myth in view of the diversion of it by literary work. And this by the use of theoretical tools of the mythocriticism of Durand and the analysis of the discourse of Maigueneau. In the same way, it will be a question of determining, moreover, the presence of these myths and their functioning within the framework of the discursive literary production of the novel, thanks to the combined contributions of mythocriticism and discourse analysis.